The development of gullies in a Mediterranean environment: The example of the Corgo gully (central Portugal) - Martins, B. (2020)
ICEER2019 - 6th International Conference on Energy and Environment Research: “Energy and environment: challenges towards circular economy”, 22 -25 July 2019, Aveiro, Portugal